Preparation method of water-soluble fluorescent carbon nanopowder
Extract lignin through ultrasound and mix with red wine polyphenols, combined with nitrogen -containing compounds and enhanced polymers, and processing through the water heat method to prepare water -soluble fluorescent carbon nano powder, solving the soluble, fluorescent strength, and stability in the existing technologies to solve the existing technologies The problem of low sexuality realizes high -efficiency and stable fluorescent properties and good water solution.
Patent Information
- Application Number
- CN202411959122.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the existing preparation methods of water-soluble fluorescent carbon nanopowder, lignin is difficult to dissolve in water, affects dispersion, has low fluorescence intensity and stability, and has a single fluorescence color, which limits its application.
Extract lignin with ultrasound auxiliary ethanol and mix with red wine polyphenols to obtain pre -processing carbon materials. Then combine with nitride -containing compounds, modified carbon material, and then combined with the enhanced polymer, processing through the water heat method, preparing water -soluble fluorescent carbon nanocrofin powder.
Improve the water -soluble, fluorescent strength and stability of water -soluble fluorescent carbon nano powder, enhance its decentralization and antioxidant performance, reduce production costs, and expand the scope of application.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescent carbon nanomaterials, and in particular relates to a method for preparing water-soluble fluorescent carbon nanopowder. Background Art
[0002] In recent years, fluorescent carbon nanopowder has attracted wide attention as a new type of fluorescent nanomaterial. Fluorescent carbon nanopowder has excellent fluorescence properties, such as no photobleaching, adjustable emission wavelength, no flicker, etc., and has good biocompatibility, low toxicity, cheap and easy to obtain. Compared with traditional metal carbon nanomaterials, fluorescent carbon nanopowder has broad application prospects in materials science, biochemistry, LED lighting and other fields. The currently reported preparation methods of fluorescent carbon nanopowder have certain limitations in carbon source cost, product yield and optical properties. Therefore, choosing a carbon source with abundant sources to synthesize fluorescent carbon nanopowder with excellent performance and improving its product yield has become the focus of attention. Biomass, as a renewable resource, has the characteristics of wide sources, large reserves, and environmental friendliness. It is an ideal material for preparing fluorescent carbon nanopowder.
[0003] In the prior art, the preparation of water-soluble fluorescent carbon nanopowder usually adopts lignin as the ideal carbon source. Although it can reduce the production cost, most of the lignin is difficult to dissolve in water, so that it cannot be evenly dispersed in the hydrothermal reaction, which affects the dispersibility of the fluorescent carbon nanopowder; in addition, the synthesized lignin fluorescent carbon nanopowder not only has low fluorescence intensity and poor stability, but also has the defect of a relatively single fluorescent color, which limits the practical application of the fluorescent carbon nanopowder. Therefore, it is necessary to further improve the water solubility, fluorescence intensity and stability of the water-soluble fluorescent carbon nanopowder. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a water-soluble fluorescent carbon nanopowder, wherein the pretreated carbon material is obtained by extracting lignin with ethanol with the aid of ultrasound and then mixing the pretreated carbon material with red wine polyphenols; the extraction of lignin with ethanol with the aid of ultrasound can improve the extraction efficiency and yield of lignin, and both lignin and red wine polyphenols have rich benzene ring structures and functional groups, which can further improve the fluorescence performance and stability of the fluorescent carbon nanopowder; the pretreated carbon material is combined with a nitrogen-containing compound to obtain a modified carbon material; the nitrogen, sulfur and boron elements in the nitrogen-containing compound play a synergistic role, which can further improve the fluorescent carbon nanopowder. The fluorescent performance and stability of the powder can be improved, and its fluorescence intensity can be enhanced; the modified carbon material is combined with a reinforcing polymer, and then treated by a hydrothermal method, and finally a water-soluble fluorescent carbon nanopowder is obtained; the reinforcing polymer has a good binding force with the modified carbon material, which can better improve the water solubility of the fluorescent carbon nanopowder, and help its dispersibility and stability in aqueous solution, and at the same time can improve the fluorescence intensity and stability of the fluorescent carbon nanopowder. Through a simple hydrothermal treatment, the fluorescent performance of the carbon nanopowder is further enhanced, and the production cost is reduced, the overall performance of the water-soluble fluorescent carbon nanopowder is improved, and it is environmentally friendly.
[0005] The technical problem to be solved by the present invention is as follows: In the prior art, the preparation of water-soluble fluorescent carbon nanopowder usually adopts lignin as an ideal carbon source. Although the production cost can be reduced, most of the lignin is difficult to dissolve in water, so that it cannot be evenly dispersed in the hydrothermal reaction, which affects the dispersibility of the fluorescent carbon nanopowder; in addition, the synthesized lignin fluorescent carbon nanopowder not only has low fluorescence intensity and poor stability, but also has the defect of a relatively single fluorescent color, which limits the practical application of the fluorescent carbon nanopowder. Therefore, it is necessary to further improve the water solubility, fluorescence intensity and stability of the water-soluble fluorescent carbon nanopowder.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing water-soluble fluorescent carbon nanopowder comprises the following steps: S1: After extracting lignin by ultrasound-assisted ethanol, it was mixed with red wine polyphenols to obtain pretreated carbon materials; S2: combining the pretreated carbon material in step S1 with a nitrogen-containing compound to obtain a modified carbon material; S3: combining the modified carbon material in step S2 with the reinforcing polymer, and then treating it by a hydrothermal method to finally obtain water-soluble fluorescent carbon nanopowder.
[0007] Furthermore, step S1 is specifically as follows: The dried mulberry powder is added to ethanol, and then extracted by ultrasonic treatment. After the extraction is completed, the filtrate is filtered and collected, and the collected filtrate is subjected to reduced pressure distillation at 45-55°C, and then added to deionized water to precipitate the lignin fraction, which is washed with deionized water and ether in turn, and then dissolved in a mixed solution of methanol and acetone, and then precipitated with ether to obtain purified lignin, which is evenly mixed with red wine polyphenols to finally obtain a pretreated carbon material.
[0008] Furthermore, the mass ratio of the dry mulberry powder to ethanol is 0.8-1.2:8-12.
[0009] Furthermore, the dry mulberry powder is obtained by grinding mulberry branches and passing through a 100-mesh sieve.
[0010] Furthermore, the temperature of the ultrasonic treatment is 25-30° C., and the time of the ultrasonic treatment is 50-60 min.
[0011] Furthermore, the mass ratio of the purified lignin to red wine polyphenols is 1:1.
[0012] Furthermore, step S2 is specifically as follows: The pretreated carbon material and nitrogen-containing compound in step S1 are added to an ethanol aqueous solution, and then acetic acid and formaldehyde aqueous solutions are added, the mixture is heated to 50-60°C, and stirred for reaction for 4-6 hours, and then centrifuged for 10-15 minutes. After filtering, it is washed with deionized water and finally dried at 40-50°C to obtain a modified carbon material.
[0013] During the above reaction process, the pretreated carbon material has a phenolic hydroxyl group, and the adjacent carbon atom of the phenolic hydroxyl group has an active hydrogen atom, and the nitrogen-containing compound has an amino group. The amino group in the nitrogen-containing compound can undergo a Mannich reaction with the active hydrogen atom in the pretreated carbon material in the presence of formaldehyde, thereby combining the pretreated carbon material with the nitrogen-containing compound to finally obtain a modified carbon material.
[0014] Furthermore, the mass ratio of the pretreated carbon material, the nitrogen-containing compound, the ethanol aqueous solution, the acetic acid, and the formaldehyde aqueous solution is 1.9-2.1: 0.6-0.8: 30-40: 3-5: 0.2-0.4.
[0015] Furthermore, the nitrogen-containing compound is composed of 2,4-diaminobenzenesulfonic acid and 3-aminophenylboronic acid mixed in a mass ratio of 0.8-0.9:0.4-0.5.
[0016] Furthermore, step S3 is specifically as follows: The modified carbon material, the reinforcing polymer and the aqueous sulfuric acid solution in step S2 are mixed evenly, and then immersed in an oil bath preheated to 160-170°C, and stirred for reaction for 2-2.5h. After the reaction is completed, it is cooled to room temperature, and then added to deionized water, and continued to be stirred for 25-35min, centrifuged for 10-15min, and then freeze-dried to obtain a composite carbon nanomaterial. The composite carbon nanomaterial is treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder.
[0017] In the above reaction process, the modified carbon material has phenolic hydroxyl groups and the reinforcing polymer has hydroxyl groups. The phenolic hydroxyl groups in the modified carbon material can combine with the hydroxyl groups in the reinforcing polymer. The modified carbon material and the reinforcing polymer are combined together to obtain a composite carbon nanomaterial, which is then treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder.
[0018] Furthermore, the mass ratio of the modified carbon material, the reinforcing polymer and the aqueous sulfuric acid solution is 0.8-1.2:1.8-2.2:0.03-0.05.
[0019] Furthermore, the reinforcing polymer is composed of polyethylene glycol 6000 and phosphoric acid-polyethylene glycol-carboxyl mixed in a mass ratio of 1-1.2:0.5-0.6.
[0020] Furthermore, the specific steps of the hydrothermal treatment are: The composite carbon nanomaterial is added to a sodium hydroxide solution and mixed evenly, then heated at 170-180°C for 12-14 hours, cooled to room temperature, and the pH value of the system is adjusted to 2-2.5 with a hydrochloric acid solution, and then ultrasonically treated for 25-35 minutes, centrifuged for 10-15 minutes, the obtained supernatant is filtered through a filter membrane, dialyzed with a dialysis bag, and finally freeze-dried to obtain a water-soluble fluorescent carbon nanopowder.
[0021] Furthermore, the mass ratio of the composite carbon nanomaterial to the sodium hydroxide solution is 0.9-1.1:15-20.
[0022] Furthermore, the membrane filtration is filtration through a 0.22 μm polyethersulfone membrane.
[0023] Furthermore, the molecular weight cutoff of the dialysis bag is 2000-3000Da, deionized water is used as the dialysis fluid, the dialysis time is 24-36h, and the water is changed 3-5 times.
[0024] Beneficial effects of the present invention: (1) In the technical scheme of the present invention, lignin is extracted by ultrasound-assisted ethanol and then mixed with red wine polyphenols to obtain a pretreated carbon material; the extraction of lignin by ultrasound-assisted ethanol can improve the extraction efficiency and yield of lignin, and the chemical structure of the extracted lignin is almost completely retained, with more phenolic hydroxyl groups, showing stronger antioxidant activity and good ultraviolet absorption performance; the extracted purified lignin is mixed with red wine polyphenols. Both lignin and red wine polyphenols are natural compounds with good biodegradability, biocompatibility and low cytotoxicity. Both lignin and red wine polyphenols have rich benzene ring structures and functional groups, and have strong antioxidant properties, which can protect carbon nanopowders from oxidative damage, and can further improve the fluorescence properties of fluorescent carbon nanopowders. The method improves stability and reduces production costs; the pretreated carbon material in step S1 is combined with a nitrogen-containing compound to obtain a modified carbon material; the nitrogen-containing compound is composed of a mixture of 2,4-diaminobenzenesulfonic acid and 3-aminophenylboric acid, 2,4-diaminobenzenesulfonic acid and 3-aminophenylboric acid not only have good binding force with the pretreated carbon material, but also 2,4-diaminobenzenesulfonic acid contains sulfur and nitrogen elements, and 3-aminophenylboric acid contains boron and nitrogen elements. When 2,4-diaminobenzenesulfonic acid and 3-aminophenylboric acid are combined with the pretreated carbon material, nitrogen, sulfur and boron elements play a synergistic role, which can further improve the fluorescence performance and stability of the fluorescent carbon nanopowder, and can enhance its fluorescence intensity, and obtain fluorescence of different colors by adjusting the fluorescence emission wavelength of the carbon nanopowder.
[0025] (2) In the technical solution of the present invention, the modified carbon material in step S2 is combined with a reinforcing polymer, and then treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder; the reinforcing polymer is composed of a mixture of polyethylene glycol 6000 and phosphoric acid-polyethylene glycol-carboxyl. The polyethylene glycol 6000, phosphoric acid-polyethylene glycol-carboxyl and the modified carbon material have good binding force, and the polyethylene glycol 6000 can enable the fluorescent carbon nanopowder to still maintain good fluorescence stability under high temperature and high pressure environment. At the same time, the polyethylene glycol 6000, as a good dispersant, can well improve the water solubility of the fluorescent carbon nanopowder, and It helps to improve its dispersibility and stability in aqueous solution. The phosphorus element in the phosphoric acid-polyethylene glycol-carboxyl group can play a synergistic role with the nitrogen element, sulfur element and boron element in the modified carbon material, further improving the fluorescence intensity and stability of the fluorescent carbon nanopowder, and has a good synergistic effect with polyethylene glycol, thereby enhancing the water solubility of the fluorescent carbon nanopowder. Finally, water-soluble fluorescent carbon nanopowder is prepared by hydrothermal treatment. Through simple hydrothermal treatment, the particle size distribution of the carbon nanopowder can be made more uniform, further enhancing the fluorescence intensity and stability of the carbon nanopowder, and reducing the production cost.
[0026] (3) In the technical scheme of the present invention, lignin is extracted by ultrasound-assisted ethanol and then mixed with red wine polyphenols to obtain a pretreated carbon material; the pretreated carbon material is combined with a nitrogen-containing compound and then combined with a reinforcing polymer, and treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder; the prepared water-soluble fluorescent carbon nanopowder has good fluorescence intensity, stability and water solubility, and can obtain fluorescence of different colors by adjusting the fluorescence emission wavelength. The fluorescent carbon nanopowder is prepared by a simple hydrothermal method, which is environmentally friendly, reduces its production cost, and expands its application range. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The specific parameters of the raw materials used in the present invention are as follows: Mulberry branches, lignin content of 21.5wt%, provided by Huzhou Academy of Agricultural Sciences (Huzhou, China); red wine polyphenols, particle size: 100 mesh, provided by Xi'an Jiatian Biotechnology Co., Ltd.; 2,4-diaminobenzenesulfonic acid, CAS number: 88-63-1, provided by Shanghai McLean Biochemical Technology Co., Ltd.; 3-aminophenylboronic acid, CAS number: 30418-59-8, provided by Shanghai McLean Biochemical Technology Co., Ltd.; polyethylene glycol 6000, CAS number: 25322-68-3, provided by Shanghai McLean Biochemical Technology Co., Ltd.; phosphoric acid-polyethylene glycol-carboxyl, purity: ≥95%, provided by Xi'an Qiyue Biotechnology Co., Ltd.
[0029] Example 1 The preparation method of water-soluble fluorescent carbon nanopowder comprises the following steps: S1: According to the mass ratio of dry mulberry powder to ethanol of 0.8:8, dry mulberry powder was added to ethanol, and then extracted by ultrasonic treatment (ultrasonic power of 500W, ultrasonic frequency of 40kHz), the temperature of ultrasonic treatment was 25℃, and the time of ultrasonic treatment was 50min, until the extract was colorless. After the extraction was completed, the filtrate was filtered and collected, and the collected filtrate was subjected to reduced pressure distillation at 45℃, and then added to deionized water (the mass of deionized water was 2 times the mass of ethanol), and the lignin fraction was precipitated, which was washed with deionized water and ether in turn (deionized water was 2 times the mass of ethanol). The mass of water is equal to that of ethanol, and the mass of ether is 1.5 times that of ethanol), and then dissolved in a mixed solution of methanol and acetone (the volume ratio of methanol and acetone is 2:1, and the mass of the mixed solution of methanol and acetone is 2 times that of ethanol), and then precipitated with ether (the mass of ether is 2 times that of ethanol) to obtain purified lignin, and the purified lignin and red wine polyphenols are evenly mixed according to the mass ratio of purified lignin to red wine polyphenols of 1:1, and finally the pretreated carbon material is obtained, wherein the dry mulberry powder is obtained by grinding mulberry branches and passing through a 100-mesh sieve; S2: according to the mass ratio of pretreated carbon material, nitrogen-containing compound, ethanol aqueous solution, acetic acid, and formaldehyde aqueous solution being 1.9:0.6:30:3:0.2, the pretreated carbon material and nitrogen-containing compound in step S1 are added to ethanol aqueous solution (the volume ratio of water to ethanol is 1:5), and then acetic acid and 35wt% formaldehyde aqueous solution are added, the mixture is heated to 50°C, and stirred for reaction for 4h, and then centrifuged at a speed of 1000rpm for 15min, filtered, washed with deionized water 3 times (the mass of deionized water each time is 60% of the mass of ethanol aqueous solution), and finally dried at 40°C for 24h to obtain a modified carbon material, wherein the nitrogen-containing compound is composed of 2,4-diaminobenzenesulfonic acid and 3-aminophenylboronic acid mixed in a mass ratio of 0.8:0.4; S3: According to the mass ratio of modified carbon material, reinforcing polymer and sulfuric acid aqueous solution of 0.8:1.8:0.03, the modified carbon material, reinforcing polymer and 90wt% sulfuric acid aqueous solution in step S2 are evenly mixed, and then immersed in an oil bath preheated to 160°C, and stirred for reaction for 2h. After the reaction is completed, it is cooled to room temperature, and then added to deionized water (the mass of deionized water is 10 times the mass of the modified carbon material), and continued to stir for 25min, and then centrifuged at a speed of 2000rpm for 15min, and finally freeze-dried at minus 20°C to obtain a composite carbon nanomaterial, and the composite carbon nanomaterial is treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder, wherein the reinforcing polymer is composed of polyethylene glycol 6000 and phosphoric acid-polyethylene glycol-carboxyl in a mass ratio of 1:0.5; The specific steps of hydrothermal treatment are: According to the mass ratio of the composite carbon nanomaterial and the sodium hydroxide solution being 0.9:15, the composite carbon nanomaterial was added to a 2 mol / L sodium hydroxide solution and mixed evenly, then heated at 170°C for 12 h, cooled to room temperature, and the pH value of the system was adjusted to 2 with a 12 mol / L hydrochloric acid solution to precipitate the unreacted composite carbon nanomaterial. The mixture was then ultrasonically treated for 25 min (ultrasonic power of 200 W, ultrasonic frequency of 40 kHz), centrifuged at 5000 rpm for 15 min, and the obtained supernatant was filtered through a 0.22 μm polyethersulfone membrane, and then dialyzed with a dialysis bag with a molecular weight cutoff of 2000 Da. Deionized water was used as the dialysate, the dialysis time was 24 h, the water was changed 3 times, and finally freeze-dried at minus 15°C to obtain a water-soluble fluorescent carbon nanopowder.
[0030] Example 2 The preparation method of water-soluble fluorescent carbon nanopowder comprises the following steps: S1: According to the mass ratio of dry mulberry powder to ethanol of 1:10, dry mulberry powder was added to ethanol, and then extracted by ultrasonic treatment (ultrasonic power of 500W, ultrasonic frequency of 40kHz), the temperature of ultrasonic treatment was 28℃, and the time of ultrasonic treatment was 55min, until the extract was colorless. After the extraction was completed, the filtrate was filtered and collected, and the collected filtrate was distilled under reduced pressure at 50℃, and then added to deionized water (the mass of deionized water was 2 times the mass of ethanol), and the lignin fraction was precipitated, which was washed with deionized water and ether (deionized water) in turn. The mass of water is equal to that of ethanol, and the mass of ether is 1.5 times that of ethanol), and then dissolved in a mixed solution of methanol and acetone (the volume ratio of methanol and acetone is 2:1, and the mass of the mixed solution of methanol and acetone is 2 times that of ethanol), and then precipitated with ether (the mass of ether is 2 times that of ethanol) to obtain purified lignin, and the purified lignin and red wine polyphenols are evenly mixed according to the mass ratio of purified lignin to red wine polyphenols of 1:1, and finally the pretreated carbon material is obtained, wherein the dry mulberry powder is obtained by grinding mulberry branches and passing through a 100-mesh sieve; S2: according to the mass ratio of pretreated carbon material, nitrogen-containing compound, ethanol aqueous solution, acetic acid, and formaldehyde aqueous solution being 2:0.7:35:4:0.3, the pretreated carbon material and nitrogen-containing compound in step S1 are added to ethanol aqueous solution (the volume ratio of water to ethanol is 1:5), and then acetic acid and 35wt% formaldehyde aqueous solution are added, the mixture is heated to 55°C, and stirred for reaction for 5h, and then centrifuged at a speed of 1500rpm for 12min, filtered, washed with deionized water 3 times (the mass of deionized water each time is 60% of the mass of ethanol aqueous solution), and finally dried at 45°C for 24h to obtain a modified carbon material, wherein the nitrogen-containing compound is composed of 2,4-diaminobenzenesulfonic acid and 3-aminophenylboronic acid mixed in a mass ratio of 0.85:0.45; S3: According to the mass ratio of modified carbon material, reinforcing polymer and sulfuric acid aqueous solution of 1:2:0.04, the modified carbon material, reinforcing polymer and 90wt% sulfuric acid aqueous solution in step S2 are evenly mixed, and then immersed in an oil bath preheated to 165°C, and stirred for reaction for 2.2h. After the reaction is completed, it is cooled to room temperature, and then added to deionized water (the mass of deionized water is 10 times the mass of the modified carbon material), and continued to stir for 30min, and then centrifuged at a speed of 2500rpm for 12min, and finally freeze-dried at minus 15°C to obtain a composite carbon nanomaterial, and the composite carbon nanomaterial is treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder, wherein the reinforcing polymer is composed of polyethylene glycol 6000 and phosphoric acid-polyethylene glycol-carboxyl in a mass ratio of 1.1:0.55; The specific steps of hydrothermal treatment are: According to the mass ratio of the composite carbon nanomaterial to the sodium hydroxide solution of 1:18, the composite carbon nanomaterial was added to a 2 mol / L sodium hydroxide solution and mixed evenly, then heated at 175°C for 13 h, cooled to room temperature, and the pH value of the system was adjusted to 2.2 with a 12 mol / L hydrochloric acid solution to precipitate the unreacted composite carbon nanomaterial. The mixture was then ultrasonically treated for 30 min (ultrasonic power of 200 W, ultrasonic frequency of 40 kHz), centrifuged at 5500 rpm for 12 min, and the resulting supernatant was filtered through a 0.22 μm polyethersulfone membrane, and then dialyzed with a dialysis bag with a molecular weight cutoff of 2500 Da. Deionized water was used as the dialysate, the dialysis time was 30 h, the water was changed 4 times, and finally freeze-dried at minus 12°C to obtain a water-soluble fluorescent carbon nanopowder.
[0031] Example 3 The preparation method of water-soluble fluorescent carbon nanopowder comprises the following steps: S1: According to the mass ratio of dry mulberry powder to ethanol of 1.2:12, dry mulberry powder was added to ethanol, and then extracted by ultrasonic treatment (ultrasonic power of 500W, ultrasonic frequency of 40kHz), the temperature of ultrasonic treatment was 30℃, and the time of ultrasonic treatment was 60min, until the extract was colorless. After the extraction was completed, the filtrate was filtered and collected, and the collected filtrate was subjected to reduced pressure distillation at 55℃, and then added to deionized water (the mass of deionized water was 2 times the mass of ethanol), and the lignin fraction was precipitated, which was washed with deionized water and ether in turn (deionized water was 2 times the mass of ethanol). The mass of water is equal to that of ethanol, and the mass of ether is 1.5 times that of ethanol), and then dissolved in a mixed solution of methanol and acetone (the volume ratio of methanol and acetone is 2:1, and the mass of the mixed solution of methanol and acetone is 2 times that of ethanol), and then precipitated with ether (the mass of ether is 2 times that of ethanol) to obtain purified lignin, and the purified lignin and red wine polyphenols are evenly mixed according to the mass ratio of purified lignin to red wine polyphenols of 1:1, and finally the pretreated carbon material is obtained, wherein the dry mulberry powder is obtained by grinding mulberry branches and passing through a 100-mesh sieve; S2: according to the mass ratio of pretreated carbon material, nitrogen-containing compound, ethanol aqueous solution, acetic acid, and formaldehyde aqueous solution being 2.1:0.8:40:5:0.4, the pretreated carbon material and nitrogen-containing compound in step S1 are added to ethanol aqueous solution (the volume ratio of water to ethanol is 1:5), and then acetic acid and 35wt% formaldehyde aqueous solution are added, the mixture is heated to 60°C, and stirred for reaction for 6 hours, and then centrifuged at a speed of 2000rpm for 10 minutes. After filtering, it is washed with deionized water 3 times (the mass of deionized water each time is 60% of the mass of ethanol aqueous solution), and finally dried at 50°C for 24 hours to obtain a modified carbon material, wherein the nitrogen-containing compound is composed of 2,4-diaminobenzenesulfonic acid and 3-aminophenylboronic acid mixed in a mass ratio of 0.9:0.5; S3: According to the mass ratio of modified carbon material, reinforcing polymer and sulfuric acid aqueous solution of 1.2:2.2:0.05, the modified carbon material, reinforcing polymer and 90wt% sulfuric acid aqueous solution in step S2 are evenly mixed, and then immersed in an oil bath preheated to 170°C, and stirred for reaction for 2.5h. After the reaction is completed, it is cooled to room temperature, and then added to deionized water (the mass of deionized water is 10 times the mass of the modified carbon material), and continued to stir for 35min, and then centrifuged at a speed of 3000rpm for 10min, and finally freeze-dried at minus 10°C to obtain a composite carbon nanomaterial, and the composite carbon nanomaterial is treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder, wherein the reinforcing polymer is composed of polyethylene glycol 6000 and phosphoric acid-polyethylene glycol-carboxyl in a mass ratio of 1.2:0.6; The specific steps of hydrothermal treatment are: According to the mass ratio of the composite carbon nanomaterial to the sodium hydroxide solution of 1.1:20, the composite carbon nanomaterial was added to a 2 mol / L sodium hydroxide solution and mixed evenly, then heated at 180°C for 14 h, cooled to room temperature, and the pH value of the system was adjusted to 2.5 with a 12 mol / L hydrochloric acid solution to precipitate the unreacted composite carbon nanomaterial. The mixture was then ultrasonically treated for 35 min (ultrasonic power of 200 W, ultrasonic frequency of 40 kHz), centrifuged at 6000 rpm for 10 min, and the obtained supernatant was filtered through a 0.22 μm polyethersulfone membrane, and then dialyzed with a dialysis bag with a molecular weight cutoff of 3000 Da. Deionized water was used as the dialysate, the dialysis time was 36 h, the water was changed 5 times, and finally freeze-dried at minus 10°C to obtain a water-soluble fluorescent carbon nanopowder.
[0032] Comparative Example 1 The difference between this comparative example and Example 3 is that, when preparing the water-soluble fluorescent carbon nanopowder, in step S1, the lignin is extracted by ethanol without ultrasonic treatment, and the remaining steps and raw materials are the same as those in Example 3; S1: According to the mass ratio of dry mulberry powder to ethanol of 1.2:12, dry mulberry powder is added to ethanol, and then extracted at 30°C for 60 minutes until the extract is colorless. After the extraction is completed, the filtrate is filtered and collected, and the collected filtrate is distilled under reduced pressure at 55°C, and then added to deionized water (the mass of deionized water is twice the mass of ethanol), and the lignin fraction is precipitated, which is washed with deionized water and ether in turn (the mass of deionized water is equal to the mass of ethanol, and the mass of ether is 1.5 times the mass of ethanol), and then dissolved in a mixed solution of methanol and acetone (the volume ratio of methanol and acetone is 2:1, and the mass of the mixed solution of methanol and acetone is twice the mass of ethanol), and then precipitated with ether (the mass of ether is twice the mass of ethanol) to obtain purified lignin, and according to the mass ratio of purified lignin to red wine polyphenols of 1:1, the purified lignin and red wine polyphenols are evenly mixed to finally obtain the pretreated carbon material, wherein the dry mulberry powder is obtained by grinding mulberry branches and passing through a 100-mesh sieve.
[0033] Comparative Example 2 The difference between this comparative example and Example 3 is that when preparing the water-soluble fluorescent carbon nanopowder, the red wine polyphenols in step S1 are replaced by tea polyphenols, and the remaining steps and raw materials are the same as those in Example 3; S1: According to the mass ratio of dry mulberry powder to ethanol of 1.2:12, dry mulberry powder was added to ethanol, and then extracted by ultrasonic treatment (ultrasonic power of 500W, ultrasonic frequency of 40kHz), the temperature of ultrasonic treatment was 30℃, and the time of ultrasonic treatment was 60min, until the extract was colorless. After the extraction was completed, the filtrate was filtered and collected, and the collected filtrate was distilled under reduced pressure at 55℃, and then added to deionized water (the mass of deionized water was 2 times the mass of ethanol), and the lignin fraction was precipitated, which was washed with deionized water and ether in turn (deionized water was 2 times the mass of ethanol). The mass of ionized water is equal to that of ethanol, and the mass of ether is 1.5 times that of ethanol), and then dissolved in a mixed solution of methanol and acetone (the volume ratio of methanol and acetone is 2:1, and the mass of the mixed solution of methanol and acetone is 2 times that of ethanol), and then precipitated with ether (the mass of ether is 2 times that of ethanol) to obtain purified lignin, and according to the mass ratio of purified lignin to tea polyphenols being 1:1, the purified lignin and tea polyphenols are evenly mixed to finally obtain the pretreated carbon material, wherein the dry mulberry powder is obtained by grinding mulberry branches and passing through a 100-mesh sieve.
[0034] Comparative Example 3 The difference between this comparative example and Example 3 is that when preparing the water-soluble fluorescent carbon nanopowder, the nitrogen-containing compound in step S2 is replaced by 2,4-diaminobenzenesulfonic acid, and the remaining steps and raw materials are the same as those in Example 3; S2: According to the mass ratio of pretreated carbon material, 2,4-diaminobenzenesulfonic acid, ethanol aqueous solution, acetic acid and formaldehyde aqueous solution being 2.1:0.8:40:5:0.4, the pretreated carbon material and 2,4-diaminobenzenesulfonic acid in step S1 are added to ethanol aqueous solution (the volume ratio of water to ethanol is 1:5), and then acetic acid and 35wt% formaldehyde aqueous solution are added, the mixture is heated to 60°C, and stirred for reaction for 6h, and then centrifuged at 2000rpm for 10min. After filtration, it is washed with deionized water 3 times (the mass of deionized water each time is 60% of the mass of the ethanol aqueous solution), and finally dried at 50°C for 24h to obtain a modified carbon material.
[0035] Comparative Example 4 The difference between this comparative example and Example 3 is that when preparing the water-soluble fluorescent carbon nanopowder, the nitrogen-containing compound in step S2 is replaced by 3-aminophenylboric acid, and the remaining steps and raw materials are the same as those in Example 3; S2: According to the mass ratio of pretreated carbon material, 3-aminophenylboric acid, ethanol aqueous solution, acetic acid and formaldehyde aqueous solution being 2.1:0.8:40:5:0.4, the pretreated carbon material and 3-aminophenylboric acid in step S1 are added to ethanol aqueous solution (the volume ratio of water to ethanol is 1:5), and then acetic acid and 35wt% formaldehyde aqueous solution are added, the mixture is heated to 60°C, and stirred for reaction for 6h, and then centrifuged at 2000rpm for 10min. After filtration, it is washed with deionized water 3 times (the mass of deionized water each time is 60% of the mass of the ethanol aqueous solution), and finally dried at 50°C for 24h to obtain a modified carbon material.
[0036] Comparative Example 5 The difference between this comparative example and Example 3 is that when preparing the water-soluble fluorescent carbon nanopowder, the mass of the reinforcing polymer in step S3 is replaced by polyethylene glycol 6000, and the remaining steps and raw materials are the same as those in Example 3; S3: According to the mass ratio of modified carbon material, polyethylene glycol 6000 and sulfuric acid aqueous solution of 1.2:2.2:0.05, the modified carbon material, polyethylene glycol 6000 and 90wt% sulfuric acid aqueous solution in step S2 are evenly mixed, and then immersed in an oil bath preheated to 170°C and stirred for reaction for 2.5h. After the reaction is completed, it is cooled to room temperature and then added to deionized water (the mass of deionized water is 10 times the mass of the modified carbon material), and stirring is continued for 35min, and then centrifuged at 3000rpm for 10min, and finally freeze-dried at minus 10°C to obtain a composite carbon nanomaterial, and the composite carbon nanomaterial is treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder.
[0037] Comparative Example 6 The difference between this comparative example and Example 3 is that when preparing the water-soluble fluorescent carbon nanopowder, the mass of the reinforcing polymer in step S3 is replaced by phosphoric acid-polyethylene glycol-carboxyl, and the remaining steps and raw materials are synchronized with Example 3; S3: According to the mass ratio of modified carbon material, phosphoric acid-polyethylene glycol-carboxyl and sulfuric acid aqueous solution of 1.2:2.2:0.05, the modified carbon material, phosphoric acid-polyethylene glycol-carboxyl and 90wt% sulfuric acid aqueous solution in step S2 are evenly mixed, and then immersed in an oil bath preheated to 170°C and stirred for reaction for 2.5h. After the reaction is completed, it is cooled to room temperature and then added to deionized water (the mass of deionized water is 10 times the mass of the modified carbon material), and stirring is continued for 35min, and then centrifuged at 3000rpm for 10min, and finally freeze-dried at minus 10°C to obtain a composite carbon nanomaterial, and the composite carbon nanomaterial is treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder.
[0038] Comparative Example 7 The difference between this comparative example and Example 3 is that when preparing the water-soluble fluorescent carbon nanopowder, the composite carbon nanomaterial in step S3 is treated by a solvent thermal method, and the remaining steps and raw materials are the same as those in Example 3; The specific steps of the solvothermal treatment are: According to the mass ratio of composite carbon nanomaterial to acetic acid being 1.1:20, the composite carbon nanomaterial is added to acetic acid and mixed evenly, then heated at 180°C for 14 hours, cooled to room temperature, added into boiling water (the mass of boiling water is 5 times the mass of acetic acid), filtered, washed 3 times with deionized water (the mass of deionized water is equal to the mass of acetic acid each time), and finally vacuum dried at 60°C to obtain water-soluble fluorescent carbon nanopowder.
[0039] The water-soluble fluorescent carbon nanopowders prepared in Examples 1-3 and Comparative Examples 1-7 were tested for fluorescence intensity. The water-soluble fluorescent carbon nanopowders prepared in Examples 1-3 and Comparative Examples 1-7 were dissolved in deionized water at a solid-liquid ratio of 1:10 to obtain carbon nano solutions, which were then fixed to 1000 mL volumetric flasks at 20°C on a fluorescence spectrophotometer (FP-6500 fluorescence spectrometer, JASCO CORERATION, Japan) with an emission wavelength fixed at 500 nm to measure the fluorescence intensity of each sample.
[0040] The test results are shown in Table 1 below: Table 1 Fluorescence intensity of water-soluble fluorescent carbon nanopowders prepared in Examples 1-3 and Comparative Examples 1-7
[0041] It can be seen from the data in Table 1 above that, by comparing Comparative Examples 1-2 with Example 3, the lignin in step S1 is extracted by ethanol without ultrasonic treatment, or the red wine polyphenols in step S1 are replaced by tea polyphenols, and finally a water-soluble fluorescent carbon nanopowder is prepared. The test results are worse than those in Example 3, indicating that the extraction of lignin by ultrasound-assisted ethanol has better extraction efficiency and yield, and exhibits stronger antioxidant activity and ultraviolet absorption performance. The extracted purified lignin is mixed with red wine polyphenols, both of which have rich benzene ring structures and functional groups, which can further improve the fluorescence performance and stability of the fluorescent carbon nanopowder, so that the prepared water-soluble fluorescent carbon nanopowder has better fluorescence intensity; By comparing Comparative Examples 3-4 with Example 3, it can be seen that the mass of the nitrogen-containing compound in step S2 is replaced by 2,4-diaminobenzenesulfonic acid, or the mass of the nitrogen-containing compound in step S2 is replaced by 3-aminophenylboric acid, and finally a water-soluble fluorescent carbon nanopowder is prepared. The test result is worse than that of Example 3, indicating that the nitrogen-containing compound composed of a mixture of 2,4-diaminobenzenesulfonic acid and 3-aminophenylboric acid not only has a good binding force with the pretreated carbon material, but also has nitrogen, sulfur and boron elements in the nitrogen-containing compound. These elements have a synergistic effect, which can better improve the fluorescence performance and stability of the fluorescent carbon nanopowder, and has a good enhancement effect on the fluorescence intensity of the fluorescent carbon nanopowder; By comparing Comparative Examples 5-6 with Example 3, it can be seen that the mass of the reinforcing polymer in step S3 is replaced by polyethylene glycol 6000, or the mass of the reinforcing polymer in step S3 is replaced by phosphoric acid-polyethylene glycol-carboxyl, and finally a water-soluble fluorescent carbon nanopowder is prepared. The test result is worse than that of Example 3, indicating that the reinforcing polymer composed of a mixture of polyethylene glycol 6000 and phosphoric acid-polyethylene glycol-carboxyl not only has a good binding force with the modified carbon material, but also has a synergistic effect between polyethylene glycol 6000 and phosphoric acid-polyethylene glycol-carboxyl, which can better improve the water solubility and dispersibility of the fluorescent carbon nanopowder. At the same time, phosphoric acid-polyethylene glycol-carboxyl contains phosphorus, which also has a synergistic effect with the modified carbon material, further improving the fluorescence intensity and stability of the fluorescent carbon nanopowder.
[0042] By comparing Comparative Example 7 with Example 3, it can be seen that the composite carbon nanomaterial in step S3 is treated by a solvothermal method to finally prepare a water-soluble fluorescent carbon nanopowder, and its test result is worse than that of Example 3, which shows that treating the composite carbon nanomaterial by a hydrothermal method can make the particle size distribution of the carbon nanopowder more uniform, which is beneficial to improving the water solubility and dispersibility of the carbon nanopowder, and further improves the fluorescence performance and stability of the fluorescent carbon nanopowder, and has a good enhancing effect on the fluorescence intensity of the fluorescent carbon nanopowder.
[0043] It can be seen from the data in Table 1 above that the water-soluble fluorescent carbon nanopowder prepared in Examples 1-3 is compared with the water-soluble fluorescent carbon nanopowder prepared in Comparative Examples 1-7. After lignin is extracted by ultrasonic-assisted ethanol, it is mixed with red wine polyphenols to obtain a pretreated carbon material; the pretreated carbon material is combined with a nitrogen-containing compound, and then combined with a reinforcing polymer, and treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder, which meets the test performance requirements, while the water-soluble fluorescent carbon nanopowder prepared in Comparative Examples 1-7 does not meet the performance requirements. The water-soluble fluorescent carbon nanopowder prepared by the present invention has good fluorescence intensity, stability and water solubility, and can obtain fluorescence of different colors by adjusting the fluorescence emission wavelength. The fluorescent carbon nanopowder is prepared by a simple hydrothermal method, which reduces its production cost and has good environmental protection.
[0044] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0045] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing water-soluble fluorescent carbon nanopowder, characterized in that: The following steps are involved: S1: After extracting lignin by ultrasound-assisted ethanol, it was mixed with red wine polyphenols to obtain pretreated carbon materials; S2: combining the pretreated carbon material in step S1 with a nitrogen-containing compound to obtain a modified carbon material; S3: combining the modified carbon material in step S2 with the reinforcing polymer, and then treating it by a hydrothermal method to finally obtain water-soluble fluorescent carbon nanopowder.
2. The method for preparing a water-soluble fluorescent carbon nanopowder according to claim 1, characterized in that: Step S1 is specifically as follows: The dried mulberry powder is added to ethanol, and then extracted by ultrasonic treatment. After the extraction is completed, the filtrate is filtered and collected, and the collected filtrate is subjected to reduced pressure distillation at 45-55°C, and then added to deionized water to precipitate the lignin fraction, which is washed with deionized water and ether in turn, and then dissolved in a mixed solution of methanol and acetone, and then precipitated with ether to obtain purified lignin, which is evenly mixed with red wine polyphenols to finally obtain a pretreated carbon material.
3. The method for preparing a water-soluble fluorescent carbon nanopowder according to claim 2, characterized in that: The temperature of the ultrasonic treatment is 25-30° C., and the time of the ultrasonic treatment is 50-60 min.
4. The method for preparing a water-soluble fluorescent carbon nanopowder according to claim 1, characterized in that: Step S2 is specifically as follows: The pretreated carbon material and nitrogen-containing compound in step S1 are added to an ethanol aqueous solution, and then acetic acid and formaldehyde aqueous solutions are added, the mixture is heated to 50-60°C, and stirred for reaction for 4-6 hours, and then centrifuged for 10-15 minutes. After filtering, it is washed with deionized water and finally dried at 40-50°C to obtain a modified carbon material.
5. The method for preparing a water-soluble fluorescent carbon nanopowder according to claim 4, characterized in that: The mass ratio of the pretreated carbon material, the nitrogen-containing compound, the ethanol aqueous solution, the acetic acid, and the formaldehyde aqueous solution is 1.9-2.1: 0.6-0.8: 30-40: 3-5: 0.2-0.
4.
6. The method for preparing a water-soluble fluorescent carbon nanopowder according to claim 4, characterized in that: The nitrogen-containing compound is composed of 2,4-diaminobenzenesulfonic acid and 3-aminophenylboric acid mixed in a mass ratio of 0.8-0.9:0.4-0.
5.
7. The method for preparing a water-soluble fluorescent carbon nanopowder according to claim 1, characterized in that: Step S3 is specifically as follows: The modified carbon material, the reinforcing polymer and the aqueous sulfuric acid solution in step S2 are mixed evenly, and then immersed in an oil bath preheated to 160-170°C, and stirred for reaction for 2-2.5h. After the reaction is completed, it is cooled to room temperature, and then added to deionized water, and continued to be stirred for 25-35min, centrifuged for 10-15min, and then freeze-dried to obtain a composite carbon nanomaterial. The composite carbon nanomaterial is treated by a hydrothermal method to finally obtain a water-soluble fluorescent carbon nanopowder.
8. The method for preparing a water-soluble fluorescent carbon nanopowder according to claim 7, characterized in that: The enhanced polymer is formed by mixing polyethylene glycol 6000 and phosphoric acid-polyethylene glycol-carboxyl in a mass ratio of 1-1.2:0.5-0.
6.
9. The method for preparing a water-soluble fluorescent carbon nanopowder according to claim 7, characterized in that: The specific steps of the hydrothermal treatment are: The composite carbon nanomaterial is added to a sodium hydroxide solution and mixed evenly, then heated at 170-180°C for 12-14 hours, cooled to room temperature, and the pH value of the system is adjusted to 2-2.5 with a hydrochloric acid solution, and then ultrasonically treated for 25-35 minutes, centrifuged for 10-15 minutes, the obtained supernatant is filtered through a filter membrane, dialyzed with a dialysis bag, and finally freeze-dried to obtain a water-soluble fluorescent carbon nanopowder.
10. A water-soluble fluorescent carbon nanopowder prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Bio-based carbon dot, and preparation method and application thereof
CN111591974A
Method for purifying lignin
US20210179787A1